(3JgPjH GddZIs - (3CHh efUhQ eMeO Hf CMeO Hf GdGRgQj, Hf WdMI,J (B370 (3g` s
(3ChdgG (B:s
(3cJGH GdLje s
(3LRA efg hYdjg NW jGbhJ Hf YHOGddg GdQheis
(3fbd ef eShOI GdeDda hbO bhQf HfSNI CNQi ahLO HjfgG GNJdGa ai GdJbOje hGdJCNjQ MjK Cf GdeDda ZjQ HYO gPg GdeShOI QCjgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B311s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B16 - (3U (B351 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B515s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs